2023
DOI: 10.3390/educsci13060571
|View full text |Cite
|
Sign up to set email alerts
|

Is a Whole School Approach to Inclusion Really Meeting the Needs of All Learners? Home-Schooling Parents’ Perceptions

Abstract: This paper examines issues impacting parental choice for home-schooling in one state in Australia. Data were collected from 99 parents home-schooling at least one child during the 2022 academic year. Utilizing the newly developed Parent Perceptions of Home-Schooling scale, consideration was given to proactive and reactive reasons perceived by parents as impacting their decision-making. Proactive reasons consisting of philosophical beliefs and needs of the child were cited more frequently by parents who had alw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Consequently, parents are permitted to choose to educate their children themselves. Therefore, just like home schoolers in other countries, UK families choose to educate their children at home for a diverse range of reasons [8][9][10][11], seek support from various sources [12], and explore multiple routes to higher education and career paths [13]. However, studies dedicated to this area of research are scarce, and there is a notable lack of studies describing how families engaged in home education in the UK facilitate their children's learning.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, parents are permitted to choose to educate their children themselves. Therefore, just like home schoolers in other countries, UK families choose to educate their children at home for a diverse range of reasons [8][9][10][11], seek support from various sources [12], and explore multiple routes to higher education and career paths [13]. However, studies dedicated to this area of research are scarce, and there is a notable lack of studies describing how families engaged in home education in the UK facilitate their children's learning.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Jolly and colleagues' study found that most of the parents they observed implemented home education only after multiple failures to find a public school that they were satisfied with [17]. Some home-educating parents decided to opt for home education because their children who had additional learning needs were not able to fit into the mainstream school system [8,9].These parents desired to provide a better education, and they can implement a curriculum and learning environment that works specifically for their children [17,18]. In summary, home education certainly appears to provide an environment that encourages parents to exercise their autonomy in supporting their children's learning and tailoring their education to individual needs.…”
Section: Introductionmentioning
confidence: 99%
“…By nature, home-schooling is individualized and child focused, within which there are many alternative approaches to implementing home-schooling. In addition, there are many reasons why parents may choose to home-school their child [4]. These include adherence to a specific ideology (often at odds with traditional educational practices) which works to instill personal beliefs [5].…”
Section: Introductionmentioning
confidence: 99%
“…There are also many parents who chose to home-school their child as they do not feel that the traditional classroom provides stimulating, motivating, or appropriate content for them [3]. Different motivations for home-schooling can be reactive (due to reacting to a situation or circumstance) or proactive (making a deliberate choice to home-school due to strongly held beliefs) [4,5]. In Western Australia, parents who had always home-schooled their child cited proactive philosophical beliefs and the needs of the child as mostly being employed in their decision-making [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation